2007
DOI: 10.1002/jcp.21325
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the gene transcription and apoptosis mediated by TGF‐β‐Smad2/3‐Smad4 signaling

Abstract: Transforming growth factor-beta (TGF-beta) signaling is known to depend on the formation of Smad2/3-Smad4 transcription regulatory complexes. However, the signaling functions of Smad2/3-Smad4 during TGF-beta-induced responses are obscure as TGF-beta also initiates a number of other signaling pathways. In this study, we systematically assessed the contribution of TGF-beta-Smad2/3-Smad4 signaling to both target gene transcription and apoptosis. Individual Smads were selectively knocked down in Hep3B cells by sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
49
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 50 publications
7
49
0
Order By: Relevance
“…[18][19][20] As for the expression of Npnt, Tsukasaki et al reported its suppression by Smad2, 21) while the present findings demonstrated its activation by Smad4. Together, these observations led us to speculate that the Npnt expression is also regulated by a transcription co-activator protein such as CBP/p300, and mediated by the competition between Smad2 and Smad4, though additional experiments are needed to more fully reveal the mechanism details.…”
Section: Resultssupporting
confidence: 56%
“…[18][19][20] As for the expression of Npnt, Tsukasaki et al reported its suppression by Smad2, 21) while the present findings demonstrated its activation by Smad4. Together, these observations led us to speculate that the Npnt expression is also regulated by a transcription co-activator protein such as CBP/p300, and mediated by the competition between Smad2 and Smad4, though additional experiments are needed to more fully reveal the mechanism details.…”
Section: Resultssupporting
confidence: 56%
“…In accordance with our results obtained in the Nme cells used here, the data collected from these other cell types point to Smad3 as an essential mediator of responses to TGFβ. Three reports from studies in human epithelial cell lines, including keratinocytes or hepatocytes, showed that Smad3 also has a prominent role in TGFβ-mediated cell cycle arrest and apoptosis (25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…4E). Finally, we tested the expression of several TGF-␤ target genes, including Smad7, c-Myc, and Bim (32)(33)(34)(35)(36). As shown in Fig.…”
Section: Pak2 Phosphorylates Smad2 At Ser 417 and The Phosphorylationmentioning
confidence: 99%